Indonesia’s Emerging Muslim Feminism: Women Leaders on Equality, Inheritance and Other Gender Issues - Feillard, Andrée (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 1997)
In this article, whose title means